2008
DOI: 10.1590/s0044-59672008000300006
|View full text |Cite
|
Sign up to set email alerts
|

A description of mercury in fishes from the Madeira River Basin, Amazon, Brazil

Abstract: Over the last 20 years several projects carried on the Madeira River basin in the Amazon produced a great amount data on total Hg concentration in different fish species. In this paper we discuss temporal trends in Hg contamination and its relation to body weight in some of those fishes, showing that even within similar groups, such as carnivorous and non-migratory fish, the interspecies variability in Hg accumulation is considerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 13 publications
2
16
0
5
Order By: Relevance
“…For this species, 54% of the samples had detectable mercury levels and for 60% the WHO limit was exceeded. Bastos et al (2008) found 0.727 µg.g −1 for P. hemioliopterus and 0.66 µg.g −1 for P. fasciatum in the Madeira River. Legg et al (2015) describe a significant correlation between mercury found in the hair and the amount of fish consumed by people surveyed in French Guiana, mostly for those people who showed preference for the most susceptible fish species to mercury contamination, including P. fasciatum and H. aimara.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For this species, 54% of the samples had detectable mercury levels and for 60% the WHO limit was exceeded. Bastos et al (2008) found 0.727 µg.g −1 for P. hemioliopterus and 0.66 µg.g −1 for P. fasciatum in the Madeira River. Legg et al (2015) describe a significant correlation between mercury found in the hair and the amount of fish consumed by people surveyed in French Guiana, mostly for those people who showed preference for the most susceptible fish species to mercury contamination, including P. fasciatum and H. aimara.…”
Section: Discussionmentioning
confidence: 91%
“…Despite being a very popular fish in the sampled areas, this species is not very recurrent in similar studies in Guianas and Suriname, except for Maury-Brachet et al (2006), who found 2.67±0.52 µg.g −1 for Ageneiosus brevifilis in French Guiana (another species of the same genus and with the same common name in Brazil). In studies on the Madeira River, Bastos et al (2008) found the average value of 0.851 µg.g −1 for A. brevifilis. Regarding the species collected in the Jari River (P. fasciatum, P. hemioliopterus and H. armatus), all fish caught had detectable levels of mercury, but only H.armatus showed an average level above the WHO reference value.…”
Section: Discussionmentioning
confidence: 97%
“…Nesse caso, ao contrário do que se observa com os coesos da Austrália (hardsetting), país pioneiro no uso de PAM para redução de coesão (ALMEIDA, 2008), a ação da PAM aplicada isoladamente foi melhor quando comparada ao tratamento combinado (PAM + gesso).…”
Section: Resultsunclassified
“…As pesquisas recentes sobre o assunto podem ser encontradas em Almeida (2008), Almeida, Raiane e Almeida (2012), Melo (2013), Andrade (2014) e Marcelo (2015).…”
Section: Introductionunclassified
“…A bioacumulação consiste no aumento da concentração de Hg no indivíduo (NRIAGU, 1979;MEILI, 1997), e a biomagnificação consiste no aumento das concentrações de Hg entre os níveis da cadeia alimentar BASTOS et al, 2008). A estrutura e o tamanho da cadeia alimentar exercem influência na concentração de HgT e MeHg (CABANA & RASMUSSEN, 1994;KIDD et al, 2003;JARDINE et al, 2013).…”
Section: -Biomagnificação E Bioacumulação De Hg No Rio Madeiraunclassified